Sustained mitochondrial functioning in cerebral arteries after transient ischemic stress in the rat: a potential target for therapies - Rutkai, Ibolya (American Physiological Society, 2014)
The objective of the present study was to determine whether mitochondrial function in the cerebral vasculature is maintained after transient middle cerebral artery (MCA) occlusion (tMCAO) in rats. Sprague-Dawley rats were exposed to 90 min of tMCAO followed by 4 or 48 h of reperfusion. MCAs from ischemic (ipsilateral) and nonischemic (contralateral) sides were compared with control MCAs from sham-operated rats. We determined 1) vasoreactivity to diazoxide (DZ; a mitochondrial ATP-activated K(+) channel opener), ACh, bradykinin (BK), serotonin, and sodium nitroprusside; 2) levels of mitochondrial and nonmitochondrial proteins and mitochondrial DNA; and 3) vascular levels of tetramethylrhodamine ethyl ester (an indicator of mitochondrial membrane potential). All dilator responses, including those with DZ, were intact 4 h post-tMCAO. Dilator responses to ACh, BK, and sodium nitroprusside were reduced in ipsilateral MCAs at 48 h compared with contralateral MCAs, but DZ responses were comparable with control MCAs. Surprisingly, contralateral responses to ACh, BK, and serotonin were reduced compared with control MCAs at 48 h. Ipsilateral vasodilation to DZ at 48 h was eliminated by endothelial denudation and endothelial nitric oxide synthase (eNOS) inhibition but was only reduced in control MCAs. Mitochondrial proteins, phosphorylated eNOS, mitochondrial DNA, and mitochondrial membrane potential were higher in ipsilateral compared with contralateral MCAs. In conclusion, contrary to conventional wisdom, mitochondria remain functional for at least 48 h after severe ischemic stress in MCAs, and DZ-induced dilation is preserved due to maintained mitochondrial mass, probably in the endothelium, and eNOS signaling. Our findings support the concept that functioning vascular mitochondria are an unexpected target for novel stroke therapies.